The Dialogue Decalogue: Ground Rules for Interreligious Dialogue - Swidler, Leonard (Journal of Dharma, 1983)
Dialogue is a conversation on a common subject between two or more persons with differing views, the primary purpose of which is for each participant to learn from the other so that he or she can change and grow. This very definition of dialogue embodies the first commandment of dialogue, as will be expanded below.